Muhammad ibn Musa al-Khwarizmi: The Pioneer of Algorithms and His Enduring Legacy in Artificial Intelligence - I. Elamin, Mustafa Osman (Journal of Ecohumanism, 2024)
Muhammad ibn Musa al-Khwarizmi, a pivotal figure of the Islamic Golden Age, established foundational principles for modern computation and artificial intelligence (AI). This article examines his transformative contributions to mathematics, particularly his seminal work, The Compendious Book on Calculation by Completion and Balancing, which introduced algebra as a systematic discipline. Al-Khwarizmi’s development of algorithms—structured problem-solving methods—shaped medieval and contemporary computational sciences. His introduction of the Hindu-Arabic numeral system, including the concept of zero, revolutionized arithmetic, enabling advancements in science, engineering, and technology. The article highlights the profound connection between Al-Khwarizmi’s methodologies and modern AI applications, such as machine learning and neural networks, which rely on systematic algorithms. It also explores the intellectual ecosystem of the Abbasid Caliphate’s House of Wisdom in Baghdad, emphasizing its role in fostering innovation and interdisciplinary collaboration. This study challenges Eurocentric narratives, shedding light on the contributions of non-Western civilizations to modern technological paradigms. Keywords: Al-Khwarizmi, Algorithms, Algebra, Artificial Intelligence, Islamic Golden Age.